Patients' experiences and perceptions on associates of TB treatment adherence: a qualitative study on DOTS service in public health centers in Addis Ababa, Ethiopia - Zekariyas Sahile; Abenezer Yared; Mirgissa Kaba (BMC, 2018)
Abstract Background Ethiopia is one of the countries with the highest TB burdens in the world. There are multitude of challenges related to the implementation of DOTS and adherence to treatment. This study aimed to assess patients' experiences and perceptions on associates of TB treatment adherence in Addis Ababa, Ethiopia. Methods A phenomenological approach was employed to generate qualitative data through the in-depth interview of TB patients attending DOTS in two public health centers. A total of ten participants, who were purposively selected till conceptual saturation was reached, were interviewed using topic guides prepared in line with the study objectives. Interviews were tape-recorded, transcribed verbatim, and translated to English. Open Code software was used to facilitate analysis. Themes pertaining to patient, health service, therapeutic, and socioeconomic factors were developed, and findings were presented accordingly. Results Experience of missing medications was reported by a single participant. Most informants pointed out that TB is transmitted through coughing and expectorate, and prevented by letting in open air in public gatherings. However, most of them stated cold air and few mentioned contaminated food as causes of TB. Perceived risk of non-adherence to medication was among recounted reasons behind treatment adherence. Some informants also recalled to have had the intention of withdrawing medication due to perceived wellness, which they actually did not change into action. Most of the participants generally had smooth relationships with their DOTS service providers. Even if more than half of the patients preferred follow-ups by the same professional, most received DOTS service by two or more service providers. Conclusions TB treatment non-adherence was not found to be a major challenge among the study participants. Perceived risk and wellness were implied to be responsible factors for adherence. Albeit the fact that few informants encountered unethical behaviors by some health professionals, interviewed patients generally had positive evaluation of the patient-provider relationship and the DOTS service obtained. There is a need to train and monitor DOTS service providers and ensure the provision of DOTS service by the same provider throughout the treatment period of a given patient.